The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/13524585221080667
|View full text |Cite
|
Sign up to set email alerts
|

The expansion and severity of chronic MS lesions follows a periventricular gradient

Abstract: Background and Objectives: Expansion of chronic lesions in multiple sclerosis (MS) patients and recently described cerebrospinal fluid (CSF)-related gradient of tissue damage are linked to microglial activation. The aim of this study was to investigate whether lesion expansion is associated with proximity to ventricular CSF spaces. Methods: Pre- and post-gadolinium three-dimensional (3D)-T1, 3D FLAIR and diffusion tensor images were acquired from 36 relapsing-remitting MS (RRMS) patients. Lesional activity was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Several recent studies have reported that progressive increase of T1 hypointensity (whether by severity or by tissue volume) within pre-existing T2 lesions is linked to lesion expansion. progressive and significant decrease in T1 intensity within slowly expanding lesions compared to non-expanding lesions[38] [27] and more recent reports confirm that increased (non-gadolinium enhancing) T1 hypointense lesion volume is primarily restricted to chronic (pre-existing) T2 lesions [2][5] A shared pathomechanism underpinning increased MD and T1 hypointensity within ELs is corroborated by the recent observation that parallel worsening in these metrics follow a periventricular gradient [28].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Several recent studies have reported that progressive increase of T1 hypointensity (whether by severity or by tissue volume) within pre-existing T2 lesions is linked to lesion expansion. progressive and significant decrease in T1 intensity within slowly expanding lesions compared to non-expanding lesions[38] [27] and more recent reports confirm that increased (non-gadolinium enhancing) T1 hypointense lesion volume is primarily restricted to chronic (pre-existing) T2 lesions [2][5] A shared pathomechanism underpinning increased MD and T1 hypointensity within ELs is corroborated by the recent observation that parallel worsening in these metrics follow a periventricular gradient [28].…”
Section: Discussionmentioning
confidence: 86%
“…While largely automated, this technique is limited to SEL count and does not allow accurate quantitative assessment of the brain tissue damage caused by the slow-burning inflammation. Manual lesion delineation, employed in other studies, while more quantifiable, requires long periods of follow-up (due to very slow lesion progression and inherent variability of manual masking), which is beyond the duration of a typical clinical trial and may delay the application of potentially beneficial treatments [3], [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in line with previous studies that demonstrated a periventricular-related tissue injury of T2-hyperintense MS lesions. 11 16 Of note, patients with ‘high’ IgG quotients showed a greater magnitude of negative correlation with ADC values compared to patients with ‘low’ IgG quotients.…”
Section: Discussionmentioning
confidence: 91%
“… 9 , 10 Indeed, previous studies have demonstrated a CSF-related gradient with a more severe tissue matrix damage in the normal-appearing white matter (NAWM) and chronic lesions in proximity to the inner and outer surfaces of the brain. 11 16 …”
Section: Introductionmentioning
confidence: 99%